1999
DOI: 10.1524/zpch.1999.209.part_2.209
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 1-Ethyl-3-Methylimidazolium Chloroaluminates: Neutron Diffraction Measurements and ab initio Calculations

Abstract: Room temperature molten salt I Chloroaluminates structure I Neutron diffraction I Ab initio calculationsThe structures of AlCl,-l-ethyl-3-methyl-imidazolium chloride melts in the concentration range of 46-67 mol% A1C13 were measured by neutron diffraction techniques. Ab initio molecular orbital calculations (6-31G* basis set) were carried out on the isolated ions which are known to form in these melts (AlClj, ALCI7, and EMU) and some of their complexes (A1CL · · · EMI+ and Al2Cl7 ... EMU). The structures and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 17 publications
6
59
0
Order By: Relevance
“…83 Over the past ten years, great ] -made based on neutron scattering data and its direct analysis or indirect interpretation through modelling. However, for ionic liquids, apart from one study by Takahashi et al 84 where data was collected on [C 2 mim]Cl-AlCl 3 ionic liquids and was interpreted through simulation, the focus of neutron scattering experiments has been on ionic liquids with metal-free anions, 85,86 and particularly on materials with static anion configurations rather than the dynamic equilibria commonly found in the halometallate systems. Neutron scattering provides information about the total structure within liquids (or glasses) and when combined with techniques such as XAS that inform on local environments, and computational modelling should be able to provide a detailed picture about how the changes in metallate anion speciation that occur with changing mole fraction affect the bulk structural properties of ionic liquids.…”
Section: Neutron Scatteringmentioning
confidence: 99%
“…83 Over the past ten years, great ] -made based on neutron scattering data and its direct analysis or indirect interpretation through modelling. However, for ionic liquids, apart from one study by Takahashi et al 84 where data was collected on [C 2 mim]Cl-AlCl 3 ionic liquids and was interpreted through simulation, the focus of neutron scattering experiments has been on ionic liquids with metal-free anions, 85,86 and particularly on materials with static anion configurations rather than the dynamic equilibria commonly found in the halometallate systems. Neutron scattering provides information about the total structure within liquids (or glasses) and when combined with techniques such as XAS that inform on local environments, and computational modelling should be able to provide a detailed picture about how the changes in metallate anion speciation that occur with changing mole fraction affect the bulk structural properties of ionic liquids.…”
Section: Neutron Scatteringmentioning
confidence: 99%
“…Early studies on ionic liquids are limited to the chloroaluminate melts. [42][43][44][45][46][47] A number of studies treat isolated imidazolium cations but have primarily been directed toward producing parameters for use in force fields. [36,38,39,48] More recently, imidazolium-based ionic liquids have been examined in which the anion has been one or more of a halide, [BF 4 À .…”
Section: =Cmentioning
confidence: 99%
“…A number of experimental (NMR spectroscopy [176][177][178][179], vibrational spectroscopy [160,173,174,[180][181][182] and neutron diffraction [148,161,183]) studies have also been employed for investigating structures of ionic liquids, except those mentioned above. Results of another interesting characterization method, electronspray ionization mass spectroscopy, have recently revealed that an ionic liquid can form aggregates and their size depends on the solvent used and the ionic liquid concentration [184,185].…”
Section: Related Studiesmentioning
confidence: 99%